In vitro growth responses of Gynura procumbens to different medium strengths and BAP concentrations - Zainol, Nur Haida Syazana; Jamal Urus, Ayuni I'llyana; Kamarudin, Mohamad Zulfadli; Awang @ Mansor, Mohd Hakiman (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Gynura procumbens is an important medicinal plant belongs to Asteraceae family. G. procumbens is traditionally used in treatment of various ailments such as diabetes, cancer and hypertension. Due to its beneficial values, the demand for raw material of G. procumbens is keep increasing. However, the conventional propagation of G. procumbens is slow and not uniform. Hence, in vitro technique was proposed to produce massive amount of G. procumbens plantlets. The nodal segments of G. procumbens were used as explants and inoculated onto the MS media. The study was carried out by using Completely Randomized Design (CRD) with two factorials; media strength (quarter, half and full strength of MS) and BAP concentration (0, 1.25, 2.50, 3.75 and 5.00 mg/L). Based on the results, full strength MS media with 1.25 mg/L BAP produced the highest number of shoot. However, the highest yield was obtained from the full strength MS media with 3.75 mg/L BAP. The highest number of leaves, fresh and dry weight also was obtained from nodal segments cultured in full strength MS media with 3.75 mg/L BAP. For the root induction, the most suitable media was found in full strength MS media without addition of plant growth regulators. From this finding, mass production of raw materials of G. procumbens can be produced in a short time, hence, the market demand for raw materials of G. procumbens can be fulfilled for industrial purposes.